1988
DOI: 10.1002/jcb.240360407
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of immunomodulatory and therapeutic activities of interferon and interferon inducers in metastatic disease

Abstract: The mechanism of therapeutic activity of recombinant murine interferon-gamma (rMu IFN-gamma) and the IFN inducer polyinosinic-polycytidylic acid solubilized with poly-L-lysine in carboxy methyl cellulose (pICLC) in treating metastatic disease was investigated by comparing effector cell augmentation with therapeutic activity in mice bearing experimental lung metastases (B16-BL6 melanoma). Effector cell functions in spleen, peripheral blood, and lung (the organ with tumor) were tested after 1 and 3 weeks of rMu … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1990
1990
2002
2002

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…Increased CTL activity in the lung has previously been reported to be associated with decreased metastasis in mice treated with IFN-y and challenged i.v. with B16-BL6 tumor cells (Black et al, 1988), increased CTL activity in the lung strongly correlating with the therapeutic efficacy of IFN-y in the treatment of lung metastasis.…”
Section: Discussionmentioning
confidence: 84%
“…Increased CTL activity in the lung has previously been reported to be associated with decreased metastasis in mice treated with IFN-y and challenged i.v. with B16-BL6 tumor cells (Black et al, 1988), increased CTL activity in the lung strongly correlating with the therapeutic efficacy of IFN-y in the treatment of lung metastasis.…”
Section: Discussionmentioning
confidence: 84%
“…IFN-γ has immunomodulatory activities such as the augmentation of Th1 cells activity, macrophage tumoricidal activity, and natural killer cell cytotoxicity and can exert a suppression of tumor growth and pulmonary metastasis (3,4,7,26,37). The adoption of transferred tumor-specific T cells, demonstrated that secretion of IFN-γ, plays an essential role in tumor rejection (2,11,28,45).…”
Section: Discussionmentioning
confidence: 99%